2015
DOI: 10.1002/ange.201503844
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Quaternary Carbon Stereocenters: Addition of 3‐Substituted Oxindoles to Vinyl Sulfone Catalyzed by Pentanidiums

Abstract: Ap entanidium-catalyzed highly enantioselective conjugate addition of 3-alkyloxindoles to phenyl vinyl sulfone has been demonstrated. This approach allows the construction of 3,3-dialkyl-substituted oxindole frameworks with high yield and excellent enantioselectivity (up to 99 %) under simple phase-transfer conditions.Avariety of oxindoles bearing allcarbon quaternary stereogenic centers were obtained in the presence of 0.25 mol %p entanidium. Meanwhile,p racticality was illustrated by agram-scale asymmetric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…To our surprise, we found that pentanidinium could catalyze the Michael addition of 3‐alkyloxindole and vinyl phenyl sulfone with high efficiency (Scheme 5). [45] …”
Section: Pentanidinium Catalyzed Enantioselective Phase‐transfer Reac...mentioning
confidence: 99%
“…To our surprise, we found that pentanidinium could catalyze the Michael addition of 3‐alkyloxindole and vinyl phenyl sulfone with high efficiency (Scheme 5). [45] …”
Section: Pentanidinium Catalyzed Enantioselective Phase‐transfer Reac...mentioning
confidence: 99%
“…Alternatively,hydrolysis of the cyano group using Rh(COD) 2 OTf and acetaldehyde oxime in refluxing toluene gave the amide 7aa,a nd subsequent reductive cyclization gave rise to the pyrroloindoline 8aa,which is the ubiquitous core structure of awide array of biologically relevant natural products. [17] Finally,the synthetic utility of this catalytic method was clearly demonstrated by its application to the concise asymmetric synthesis of chiral spirocyclohexane oxindole derivatives [Eq. (2) in Scheme 2].…”
Section: Angewandte Chemiementioning
confidence: 99%
“…We have recently developed pentanidium27282930 and dicationic bisguanidinium ( BG ) as efficient phase-transfer3132 and ion pair catalysts3334353637. We have utilized bisguanidinium permanganate ion pair catalyst for the enantioselective oxidation of alkenes38.…”
mentioning
confidence: 99%